Analisis Pertimbangan Hakim Dalam Putusan Pada Gugatan Penggugat Eror in Persona Dalam Perkara Perjanjian Pembiayaan Multiguna Dengan Penyerahan Secara Fidusia - Rusli, Tami (Universitas Sang Bumi Ruwa Jurai, 2025)
The explanation in Law No. 42 of 1999, stipulates that every fiduciary guarantee must be officially registered with the Fiduciary Guarantee Registration Office. If the fiduciary guarantee is not registered, then the fiduciary guarantee does not have executorial power. There is a lawsuit case alleging that the defendant has committed a breach of contract on a multipurpose financing agreement with a fiduciary delivery guarantee in decision No. 4/Pdt.G.S/2024/PN Kot between PT Woori Finance Indonesia Tbk against Azimi and Rosida. In deciding the case, the judge in evaluating the Plaintiff's case is considered untenable, because it relies on the evaluation of documentary evidence presented in the form of photocopies, without the original document whose authenticity has never been shown. legal principle: when submitting a 'photocopy of a letter' as court evidence, the photocopy version must be authenticated to match the original document. So this is used as the basis for the judge's consideration in deciding this case